Neutral Sphingomyelinase-2 (NSM 2) Controls T Cell Metabolic Homeostasis and Reprogramming During Activation - De Lira, Maria Nathalia; Raman, Sudha Janaki; Schulze, Almut; Schneider-Schaulies, Sibylle; Avota, Elita (Frontiers in Molecular Biosciences, 2020)
Neutral sphingomyelinase-2 (NSM2) is a member of a superfamily of enzymes responsible for conversion of sphingomyelin into phosphocholine and ceramide at the cytosolic leaflet of plasma membrane. Upon specific ablation of NSM2, T cells proved to be hyper-responsive to CD3/CD28 co-stimulation indicating that the enzyme acts to dampen early overshooting activation of these cells. It remained unclear whether hyper-reactivity of NSM2 deficient T cells is supported by a deregulated metabolic activity in these cells. Here, we demonstrate that ablation of NSM2 activity affects metabolism of the quiescent CD4+ T cells which accumulate ATP in mitochondria and increase basal glycolytic activity. This supports enhanced production of total ATP and metabolic switch early after TCR/CD28 stimulation. Most interestingly, increased metabolic activity in resting NSM2 deficient T cells does not support sustained response upon stimulation. While elevated under steady state conditions in NSM2 deficient CD4+ T cells, the mTORC1 pathway regulating mitochondria size, oxidative phosphorylation and ATP production is impaired after 24 hours of stimulation. Taken together, the absence of NSM2 promotes a hyperactive metabolic state in unstimulated CD4+ T cells yet fails to support sustained T cell responses upon antigenic stimulation.